If f(x) = 2x + 1, and
g(x) = x - 3, then
f(g(x)) = [ ? ]x + [ ]
![If fx 2x 1 and gx x 3 then fgx x class=](https://us-static.z-dn.net/files/d79/25572c2531b3f9ab465687c9e092596c.png)
Answer:
First box +2
Second box -5
Step-by-step explanation:
Just an Example,
If f(x) = 2x + 1 and we need f(2) we would replace the x in the function with the number 2 because 2 is the domain of the function , so f(2) would become,
f(2) = 2(2) + 1
f(2) = 4 + 1 = 5
Now the question is what is f(g(x)) in this case the domain of the function is g(x). In simpler words we replace x with the function g(x) so here goes,
[tex]f(x)=2x+1\\g(x)=x-3\\f(g(x))=2(x-3)+1\\f(g(x))=2x-6+1\\f(g(x))=2x-5[/tex]
so,
f(g(x)) = 2x - 5